A Carbazole-based Fluorescent Turn-off Chemosensor for Iron (II/III) Detection in a Dimethyl Sulfoxide - Battal, Ahmet; Kassa, Solomon Bezabeh; Gultekin, Nuray Altinolcek; Tavasli, Mustafa; Onganer, Yavuz (Springer/Plenum Publishers, 2023)
We designed a novel carbazole-based chemosensor from 2-(N-hexylcarbazol-3'-yl)-pyridine-5-carbaldehyde which was named probe 7b. The main purpose of this study is to investigate whether metal ions in liquid media can be detected with probe 7b. The details were presented in this paper. First, the molecular absorption and fluorescence properties of probe 7b were characterized by spectrophotometers. Then, several methods were applied to check its sensing properties. The results showed that probe 7b has a sense towards Fe3+ ion than other interfering metal ions. The selectivity and sensitivity of probe 7b towards Fe3+ were very satisfactory to use in applications. Also, it was observed that when aqueous Fe3+ ion solutions were added to probe 7b in dimethyl sulfoxide (DMSO), the fluorescence intensity of probe 7b decreased. This situation (turn-off of emission) is due to the paramagnetic effect between probe 7b and Fe3+ ions. The limit of detection (LOD) value was found as 1.38 nM for probe 7b. This value is very small to compete with its counterparts in the literature. A real sample experiment indicated that probe 7b can detect Fe3+ ions more than other ions in real media, too. As a result, it was deduced that probe 7b is a very strong candidate to use in sensor technology.
Keywords: Carbazole Fluorescent Chemosensor Fe3+ Ion Real Sample Probe; Selective Detection; Schiff-Base; Fe3+; Sensor; Probe; Cu2+